Pemanfaatan Silase Ransum Komplit Berbasis Ampas Tebu (Bagasse), Indigofera dan Molases sebagai Pakan Alternatif - Arbiansyah, Arbiansyah; Jati, Putri; Juliantoni, Jepri; Rodiallah, Muhamad; Ramdani, Dedi; Habiyah, Umul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Bagasse has not been utilized optimally because it has low nutrient content, it was necessary to add feed ingredients such as indigofera which has high nutrition and molasses was needed for further processing utilizing anaerobic fermentation or silage. This study aims to determine the nutritional quality of complete ration silage based on bagasse, indigofera and molasses with different compositions. Silage was carried out at the Laboratory of Nutrition and Feed Technology, Faculty of Agriculture and Animal Sciences, State Islamic University of Sultan Syarif Kasim Riau. The proximate test was carried out at the Laboratory of the Center for Biological Resources and Biotechnology Research, Agricultural University of Bogor. This study used a completely randomized design with a factorial pattern consisting of 2 factors, each treatment unit was repeated 3 times. Factor A was the level of bagasse + indigofera, namely A1 = 100% bagasse + 0% indigofera; A2 = 50% bagasse + 50% indigofera; A3 = 75% bagasse + 25% indigofera and factor B was the level of molasses, namely B0 = 5% molasses and B1 = 10% molasses. The variables measured were crude fat, ash content and BETN. The data obtained were analyzed based on analysis of variance by using Duncan's test at 5% and 1%. The results of this study indicated that there was an interaction between factor A and factor B (P<0.01) on crude fat content, ash content, and BETN. Factor A had a very significant effect (P<0.01) on the crude fat content, ash content, and BETN. Factor B had a very significant effect (P<0.01) on crude fat and BETN, but did not affect the ash content. It was concluded that treatment A2, namely the composition of bagasse 50% + 50% indigofera and treatment B0, namely molasses 5%, obtained the best results.